Community dermatology: Current status and the way forward - Neelakandhan Asokan (Wolters Kluwer Medknow Publications, 2023)
Community health interventions in dermatology have the potential to deliver healthcare to large populations. Such interventions can bridge the gap between increasing demands from vast populations and limited availability and asymmetric geographical distribution of specialist doctors. This narrative review aims to delineate various areas in which community dermatology initiatives are useful, the different approaches used, and the factors which could determine their effectiveness. We did a PubMed search using the search terms, "Community Health Services"[Mesh]) AND "Dermatology"[Mesh]. A further literature search was performed by cross-referencing these articles. In addition to its primary purpose of increasing access, community involvement can augment medical education, foster research, and help to develop more patient-centered clinical guidelines, understand disease trends and influences of the environment on various diseases, and formulate population-centered health policy. Task shifting, development of culture-sensitive and gender-sensitive community healthcare teams, disease-specific patient support groups, and use of advances in technology such as telemedicine are some of the important methods used in community dermatology. Task shifting may be performed at different levels - general practitioners, pharmacists, nurses, and community health workers. Community interventions harness volunteerism among health professionals as well as various stakeholders in the community. Partnering with non-governmental organizations, involving members of the community, and being a part of a long-term public health program help to sustain community interventions. The interventions should adapt to the ethical and cultural norms of the community. Continuity of care, fidelity, and evidence support are crucial for the success of community interventions in dermatology.